Minecraft amazing bite-size builds : over 20 awesome mini-projects. (Del Rey, an imprint of Random House, a division of Penguin Random House LLC, 2022)
Providing exploded views, a step-by-step guide, and detailed instructions, this latest volume in the series shows readers how to design, build and create twenty new Minecraft mini-projects.